Effect of Microwave Pretreatment on Gaharu Essential Oil Using Hydrodistillation Method - Nurhaslina Che Radzi; Filzah Anati Kasim (Universitas Gadjah Mada, 2020)
Gaharu wood produces an expensive essential oil due to its fragrance and chemical compounds. Normally, the black color wood is used for the extraction of oil because it contains high resin. However, the cost of this resinous wood is very expensive. Therefore, in this study, the raw material with low resin content (identified by the white color of the wood) will be used for the extraction of oil. However, hydrodistillation alone will not produce satisfactory volume. Thus, pretreatment is needed to enhance the amount of essential oil. This paper aims to investigate the effect of microwave pretreatment on gaharu essential oil extraction using the hydrodistillation method for the lower grade wood. The gaharu wood was pre-treated with microwave irradiation power of 800 kW at three different durations which were 1, 2 and 3 min. Later, extraction was performed using the hydrodistillation method for 30 h. The chemical composition of the oil was analyzed using gas chromatography-mass spectrometry (GCMS). The results show that microwave pretreatment produced higher yield (0.0379 wt.%) of gaharu essential oil compared to the extraction of the non-pretreated wood (0.0286 wt.%) in which the increase was 24.55%. The three minutes pretreatment time produced the largest amount of oil (0.0877 wt.%). The outcomes of this study indicated the increase of chemical components of gaharu essential oils such as (+)-Epi-bicyclosesquiphellandrene, gurjunene, α-farnese, estragole, guaiene, valencene, spathulenol, α-cubebene and (-)-Spathulenol in the extraction of the pre-treated wood compared to the non-pretreated one.